ประสิทธิภาพและประสิทธิผลของการรับนิสิตระดับปริญญาตรีของสาขาวิชากายภาพบำบัด คณะสหเวชศาสตร์ มศว (EFFECTIVENESS AND EFFICACY OF UNDERGRADUATE STUDENT ADMISSION OF PHYSICAL THERAPY DIVISION, FACULTY OF HEALTH SCIENCE, SRINAKHARINWIROT UNIVERSITY) - วิริยะธารากิจ, นิตยา; ถาวร, นิธินันท์; เหลาทอง, ชินตา; สวัสดี, อนุศักดิ์ (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2015)
สาขาวิชากายภาพบำบัด คณะสหเวชศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ มีการรับนิสิตเข้าศึกษาระดับปริญญาตรีสองระบบ คือ จากการสอบตรงตามระบบการคัดเลือกของมหาวิทยาลัยศรีนครินทรวิโรฒและตามระบบกลาง (Admissions) จากสำนักงานคณะกรรมการการอุดมศึกษา เพื่อส่งเสริมให้ระบบการคัดเลือกนี้บรรลุเป้าหมายและมีคุณภาพ การศึกษานี้จึงมีวัตถุประสงค์เพื่อวิเคราะห์ประสิทธิภาพและประสิทธิผลของการรับนิสิตสาขาวิชากายภาพบำบัด คณะสหเวชศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ ผลการศึกษา การสอบตรงปีการศึกษา 2553 ถึง 2555 นิสิตที่ผ่านการสอบทั้งหมดมารายงานตัวเป็นนิสิต จำนวน 33 คน (21.8%) 27 คน (18.4%) และ 16 คน (8.8%) ตามลำดับ ส่วนนิสิตที่รับจากระบบกลางมีจำนวนนิสิตมากกว่าแผนการรับที่กำหนด โดยนิสิตทั้งหมดในปีการศึกษา 2555 มีคะแนนผลสัมฤทธิ์ทางการเรียนของปีการศึกษาที่ 1 ตั้งแต่ระดับพอใช้ (เกรด ซี) ขึ้นไป ยกเว้น นิสิตจำนวน 2 คน (1.14%) ที่รับจากระบบกลางมีคะแนนผลสัมฤทธิ์ทางการเรียนของปีการศึกษาที่ 1 น้อยกว่าระดับพอใช้ สรุปการรับนิสิตระดับปริญญาตรีของสาขาวิชากายภาพบำบัด คณะสหเวชศาสตร์ มศว ประสบผลสำเร็จ โดยประสิทธิภาพของกระบวนการรับนิสิต คือ การได้นิสิตที่มีคุณภาพ มีความรู้ผ่านตามเกณฑ์ที่กำหนด แม้ว่าจำนวนนิสิตจากระบบรับตรงได้น้อยกว่า แผนการรับ ประสิทธิผลที่ชัดเจน คือ การได้นิสิตที่สามารถรับการพัฒนาให้มีระดับความรู้ตามวัตถุประสงค์ของหลักสูตร ทั้งนี้ สาขาวิชากายภาพบำบัดควรเพิ่มนโยบายและกลยุทธ์ที่ทำให้สามารถได้จำนวนนิสิตที่มีคุณภาพตามเป้าหมายที่ต้องการ โดยเฉพาะจากระบบสอบตรงตามระบบการคัดเลือกของมหาวิทยาลัยศรีนครินทรวิโรฒ คำสำคัญ: คุณภาพ ระบบสอบตรง การคัดเลือกนิสิต อุดมศึกษา Physical Therapy Division, Faculty of Health Science, Srinakharinwirot University, has two modes of admission to the undergraduate program: one through the entrance examination administered by the University, the other through that administered by the Office of the Higher Education Commission, Ministry of Education. This study aimed to analyze the effectiveness and the efficacy of the two admission modes so that the findings can be applied to achieve the goals of the admission process and to enhance its quality. The results of the admission from 2010 to 2012 academic years showed that of all the qualified students who had passed the University’s admission system only 33 (21.8%), 27 (18.4%) and 16 (8.8%) students registered for the program respectively. Whereas students registered from the admission of the Office of the Higher Education commission had greater numbers than admission plans. It was found that all of the first-year students admitted in 2012 academic year passed the achievement examination with a C grade and above, except two of them (1.14%) receiving a grade below C. These two students were accepted to the program through the admission of the Office of the Higher Education commission. Conclusions: Process of Admission achieved success. Its effectiveness of the admission process was evident in the achievement examination results of the qualified students; though, the numbers of students enrolled from University’s admission system were all less than the plans. The efficacy was clearly shown from the students with potential for academic success, realizing the objectives of the curriculum. However, It should be noted that the Physical Therapy Division should improve its present policy and strategies in order to increase the qualified enrollments, especially though the University admission. Keywords: quality, university admission, enrollments, higher education